1987
DOI: 10.1002/zoo.1430060404
|View full text |Cite
|
Sign up to set email alerts
|

In vitro capacitation of Siberian tiger spermatozoa

Abstract: Three experiments were designed to determine optimum conditions for capacitation of Siberian tiger (Puntheru tigris ultuicu) sperm in vitro using the zona-free hamster egg sperm penetration assay (SPA) as a verification of capacitation. Sperm collected from a 9-year-old captive Siberian tiger were subjected to different in vitro washing conditions, preincubation times, and temperatures to induce capacitation. Sperm were able to penetrate zona-free hamster ova after 2 hours preincubation at 37°C but not at time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The capacitation results of these experiments using fresh spermatozoa from 5 Siberian tigers confirm the preliminary results reported previously on one tiger (Byers et al, 1987), namely in-vitro capacitation of Siberian tiger spermatozoa requires a 2-h preincubation period at 37°C in capaci¬ tation medium or in seminal plasma. The decapacitation factor in the seminal plasma of several other species (rabbit: Chang, 1957; (1988) reported that removal of seminal plasma was not required for in-vitro capacitation of domestic cat spermatozoa before penetration of zona-free hamster ova.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The capacitation results of these experiments using fresh spermatozoa from 5 Siberian tigers confirm the preliminary results reported previously on one tiger (Byers et al, 1987), namely in-vitro capacitation of Siberian tiger spermatozoa requires a 2-h preincubation period at 37°C in capaci¬ tation medium or in seminal plasma. The decapacitation factor in the seminal plasma of several other species (rabbit: Chang, 1957; (1988) reported that removal of seminal plasma was not required for in-vitro capacitation of domestic cat spermatozoa before penetration of zona-free hamster ova.…”
Section: Discussionsupporting
confidence: 90%
“…hCG (Sigma) 55 h later. At 17 h after hCG the animals were killed, oocytes harvested and zona-free oocytes prepared as described by Byers et al (1987). The zona-free eggs were then washed 3 times and 20 eggs were added to each 50 µ droplet of spermatozoa (prepared as described below for each experiment) under mineral oil.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the conditions for in vitro capacitation of domestic cat sperm are less complex than for other species that require exposure to a hypertonic medium [281, to heparin [261, or to a high calcium concentration [25]. On the contrary, removing seminal plasma is unnecessary for cat oocyte penetration; simple semen dilution is sufficient for gamete interaction in the domestic cat [1] and tiger (Panthera tigris) [29]. The discovery that domestic cat sperm exhibit a relatively low frequency of spontaneous acrosomal loss in vitro also differs from that observed in sheep [30] and dog [31] sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Siberian tigers are the largest of the tiger subspecies and 366-406 Siberian tigers exist in the wild (WWF). There are many researches in favor of saving tigers (Tilson and Seal, 1986;Byers et al, 1987;Donoghue et al, 1990Donoghue et al, , 1992Miller et al, 1990). However, there population has gradually been reduced (International Union for Conservation of Nature and Natural Resources, IUCN).…”
Section: Introductionmentioning
confidence: 99%